Bibliographical Note: A. G. C. Savvides, “No rest for the wicked” [Isaiah 48:22 & 57:21]. On Isaac Ducas Comnenus’ Cypriot “separatist” state (A.D.1184/5-1191): The last of the Cypriot revolts against Byzantium (Papazissis Publishers: Athens, 2019). - EDBURY, Peter (Byzantina Symmeikta, 2021)
A. G. C. Savvides, “No rest for the wicked” [Isaiah 48:22 & 57:21]. On Isaac Ducas Comnenus’ Cypriot “separatist” state (A.D.1184/5-1191): The last of the Cypriot revolts against Byzantium (Papazissis Publishers: Athens, 2019).